A study on the banking procedures of the general banking department of Trust Bank Limited, Banani Branch - Anjum, Abrar Mahmud (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.